1981
DOI: 10.3109/01050398109076174
|View full text |Cite
|
Sign up to set email alerts
|

Click Polarity Inversion Effects Upon the Human Brainstem Auditory Evoked Potential

Abstract: Parameters of the brainstem auditory evoked potentials (BAEPs) to high-intensity clicks of initial rarefaction (R) and condensation (C) phases differed. The amplitudes of Waves I, II and IV were greater with R clicks, while that of Wave V was greater with C clicks. The peak-latencies of Waves I and VI were shorter with R clicks and those of the remaining components tend to shorten with C clicks. At low stimulus intensities the preserved BAEP components (Waves III, V and VI) did not change noticeably with click… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 13 publications
2
6
0
1
Order By: Relevance
“…On the other hand, there was no polarity effect, although a trend can be noted. For wave I, rarefaction clicks tended to yield a shorter latency, a finding which agrees with results reported by Emerson et al (1982), Kevanishvili and Aphonchenko (1981), Lynn, Robinson, and Schwan (1985), and Ruth et al (1982). There was virtually no difference between rarefaction and condensation clicks for wave III which is consistent to the results of Lynn et al (1985) and Ruth et al (1982).…”
Section: Amplitude Ratio V/isupporting
confidence: 83%
See 1 more Smart Citation
“…On the other hand, there was no polarity effect, although a trend can be noted. For wave I, rarefaction clicks tended to yield a shorter latency, a finding which agrees with results reported by Emerson et al (1982), Kevanishvili and Aphonchenko (1981), Lynn, Robinson, and Schwan (1985), and Ruth et al (1982). There was virtually no difference between rarefaction and condensation clicks for wave III which is consistent to the results of Lynn et al (1985) and Ruth et al (1982).…”
Section: Amplitude Ratio V/isupporting
confidence: 83%
“…Kevanishvili and Aphonchenko (1981) reported that latency was little affected by the polarity change. The .…”
Section: The Effects Of Stimulus Polarity On the Abrmentioning
confidence: 99%
“…For the ABR the available informa tion is incomplete. Most investigators used only C and R clicks (with duration times of 0.02 ms [Coats and Martin, 1977], 0.01 ms [Hughes et al, 1981], 0.1 ms [Stockard et al, 1979], 0.125 ms [Rosenhamer et al, 1978] or 0.120 ms [Kevanishvili and Alphonchenko, 1981]), giving very short stimulus phase shifts. In that way the possible effects on the response can submerge in the usual latency variability (or jitter) of the neural response; so they saw only a minimal (Stockard et al [1979]: 0.07 ms; Rosenhamer et al [1978]: 0.08 ms) or no significant effect upon the latency of waves I and III.…”
Section: Discussionmentioning
confidence: 99%
“…Zum Einfluss von Sog-gegenüber Druckreizen auf das BAEP gibt es vielfache Untersuchungen; so wurde bereits 1975 von Ornitz und Walter [3] überdeutliche Unterschiede in den Latenzen der Potentiale insbesondere der Welle V bei einigen Normalpersonen berichtet. Andere Autoren wie Rosenhammer et al [4], Stockard et al [5], Kevanishvili und Aphonchenko [6], Tietze et al [7] Welle V zwischen rc-und cc-Stimulation. Maurer [9] stellte bei einer grossen Gruppe Normalhörender signi fikant kürzere Wellenlatenzen der mittels Sogreizen aus gelösten BAEP fest und beschrieb Konfigurationsabhän gigkeiten des IV/V-Komplexes.…”
Section: Introductionunclassified